ARTIFICIAL INTELLIGENCE AND WOMEN’S RIGHTS: ARE WE UP AGAINST A SEXIST ALGORITHM? (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The algorithms used by AI systems are developed by scientists and computer scientists, who train the algorithm on the basis of a set of data, which - sometimes - can hide their own biases and errors. One of the most widespread and pervasive prejudices is that of gender, which tends to manifest itself in a variety of contexts, from automated decision-making processes in human resources and credit access systems to its use in so-called ‘revenge porn’, whose victims are, in fact, mostly women. Such forms of discrimination result in a violation of the principles and freedoms that underpin our democracies. Therefore, to struggle against the perpetuation of such stereotypes and prejudices, it is important to be awareness-raising and to address diversity as a fundamental priority of policies and institutional structures.
Keywords: Algorithms; artificial intelligence; principle of equality; discrimination; women